HEARING LOSS AND RETINOPATHY IN RELATION TO GLYCEMIC LEVELS AMONG DIABETIC PATIENTS (The Research of Medical Science Review, 2025)
Diabetes mellitus is a long-term condition of the metabolism system where the blood glucose or sugar levels are too high in the blood, something that can cause a host of complications that affect almost every organ system in the body. Other less- discussed complications include hearing loss and retinopathy that avert the quality of life of a diabetic patient. The purpose of this research will be to establish a correlation between glycemic activity on one hand and hearing impairment and retinopathy on the other among people with diabetes. A descriptive survey was conducted among 500 diabetic patients attending endocrinology clinics selected from three teaching hospitals. Blood glucose was determined by HbA1c levels, hearing loss by audiogram, and retinopathy by fundoscopic examination. The findings revealed that the prevalence of both hearing loss and retinopathy was associated with HbA1c > 7%. Hearing loss was significantly higher among patients with poor glycemic control, that is, those having HbA1c > 7% with a 35% incidence as compared with a 22.5% incidence among those with good glycemic control, that is, HbA1c < 7%. Likewise, for retinopathy, the patient with poor glycemic control had 50% as against 25% of those with optimal glycemic control. Indeed, logistic regression tests further showed that poor glycemic control was significantly associated with increased odds of developing both complications. This investigation also emphasizes the significance of good glycemic control in avoiding complications in the ear and the eye in diabetic patients. To prevent these negative effects, Weldingvik’s recommendation of early detection and intervention is advised. More longitudinal observation is needed to determine the effect relationship between glycemia and both auditory and retinal injury and investigate pathophysiological processes by which hyperglycemia causes the outcomes.